Governance, religious assurance and Islamic banks: do Shariah boards effectively serve? - Mohd Haridan, Nurfarahin; Sheikh Hassan, Ahmad Fahmi; Karbhari, Yusuf (Springer, 2018)
This study examines the quality of governance and religious assurance provided by Shariah boards (SBs) when undertaking the crucial compliance review required in fulfilling the expected ethical and social legitimacy of Islamic banks. To better understand the complex behavioural processes, we explore the governance role of SBs and assess issues related to competence, effectiveness and independence in the light of the newly adopted 2011 Malaysian Shariah Governance Framework (SGF). A series of semi-structured interviews were undertaken with key individuals in two well-established fully-fledged Malaysian Islamic banks. Our findings reveal that the newly implemented SGF has generally brought about some of the benefits hoped for by its regulatory architects. We find the quality of religious assurance to have been enhanced due to the emphasis placed on religious audit giving rise to improved credibility. However, we report the compliance review process to be inadequately undertaken with SBs still excessively reliant on internal officers implying possible independence compromise. We highlight concerns relating to (1) the general level of competency of individual SB members; (2) lack of technical banking and finance knowledge; and (3) SB members generally fulfilling a ceremonial role rather than undertaking vigilant monitoring. Our findings lead us to question the full impact of the new 2011 SGF and query the value and effectiveness of SBs. We make the call for the establishment of external religious auditors to render compliance assurance which could provide the much-needed impetus to improve governance and increase market and stakeholder confidence.